Postpartum hemorrhage: incidence, risk factors, and outcomes in a low-resource setting - Ngwenya S (International Journal of Women's Health, 2016)
Solwayo Ngwenya1–3 1Department of Obstetrics and Gynaecology, Mpilo Central Hospital, Bulawayo, Zimbabwe; 2Royal Women’s Clinic, Bulawayo, Zimbabwe; 3Medical School, National University of Science and Technology, Matabeleland, Zimbabwe Background: Primary postpartum hemorrhage (PPH) is defined as blood loss from the genital tract of 500 mL or more following a normal vaginal delivery (NVD) or 1,000 mL or more following a cesarean section within 24 hours of birth. PPH contributes significantly to maternal morbidity and mortality worldwide. Women can rapidly hemorrhage and die soon after giving birth. It can be a devastating outcome to many young families. Women giving birth in low-resource settings are at a higher risk of death than their counterparts in resource-rich environments. PPH is a leading cause of maternal deaths globally, contributing to a quarter of the deaths annually. Aims: This study aims 1) to document the incidence, risk factors, and causes of PPH in a low-resource setting and 2) to document the maternal outcomes of PPH in low-resource setting. Methods: This was a retrospective descriptive cohort study carried out at Mpilo Central Hospital, a tertiary referral government hospital in a low-resource setting in Bulawayo, Zimbabwe. Data were obtained from the labor ward birth registers for patients who had a diagnosis of PPH during the period from January 1, 2016 to June 30, 2016. The case notes were retrieved and the demographic, clinical, and outcome data were gathered. Blood loss was estimated postdelivery by the attending clinician – either a midwife or a doctor. At this maternity unit, blood loss is not measured but estimated owing to prevailing resource constraints. The SPSS Version 21 statistical tool was used to calculate the mean and standard deviation (SD) values. Simple statistical tests were used on absolute numbers to calculate percentages. Results: There were 4,567 deliveries at the institution during the period from January 1, 2016 to June 30, 2016. There were 74 cases of PPH during the study period. The incidence of primary PPH was 1.6%. The mean age was 27.7 years (SD ±6.9), mean gestational age was 38.6 weeks gestation (SD ±2.2), and mean birth weight was 3.16 kg (SD ±0.65) for the studied group of patients. Three-quarters (75.7%) of the cases had NVD. The majority of the cases (77.0%) had an identifiable risk factor for developing primary PPH. The most identifiable risk factor for primary PPH was pregnancy-induced hypertension followed by prolonged labor. Uterine atony was the most common cause of postpartum hemorrhage (82.4%). The women who delivered by NVD, who were diagnosed with a PPH, and who lost an estimated 500–1,000 mL of blood were 73.2%; 25% lost 1,000–1,500 mL of blood, and 1.8% lost more than 1,500 mL of blood. The women who delivered by lower-segment cesarean section, who were diagnosed with a PPH, and who lost an estimated 1,000–1,500 mL of blood were 77.8%, and 22.2% bled an estimated 1,500 mL of blood or more. The majority of the cases of primary PPH (94.6%) survived the condition and 5.4% died. Conclusion: The incidence of PPH at Mpilo Central Hospital was 1.6% during the study period, lower than that reported elsewhere in similar setting in the literature. This study, therefore, is important as it documents for the first time for this maternity unit and for a Zimbabwean setting, the incidence of one of the most important causes of global maternal deaths. Future studies should involve the effect on maternal outcomes of PPH following widespread introduction of misoprostol therapy into practice. This data can help in mobilizing global efforts to improve women’s health. Keywords: causes, uterotonics, avoidable deaths, maternal outcomes, low-resource settings